Hoffnung für einige Nordseefischbestände - Dornheim, Holger; Wegner, Gerd (1977)
In the first quarter of 1997 R.V. “Walther Herwig III” took part in the internationally (ICES) coordinated International Bottom Trawl Survey (IBTS) in the North Sea. A total of 365 half-hour tows using a standardized GOV-net were made by seven research vessels in order to determine the strength of incoming yearclasses of cod, haddock, whiting, Norway pout, herring, sprat, and mackerel. Overall results, though preliminary show a considerable increase of the index figures for cod, Norway pout, herring, and mackerel whereas the indices for haddock, sprat, and whiting indicate lower recruitment figures. Water temperatures and salinity values were unhomogeneously below and above of the longterm mean. Johann Heinrich von Thünen-Institute, Federal Research Institute for Rural Areas, Forestry and Fisheries began publishing the Informationen aus der Fischereiforschung = Information on Fishery research in 2010.